HUBUNGAN TINGKAT PENGETAHUAN TENTANG SENAM KAKI DENGAN TINDAKAN PENCEGAHAN KOMPLIKASI KAKI PADA PASIEN DIABETES MELLITUS - Yulia, Aida (LPPM Universitas Muhammadiyah Sumatera Barat, 2020)
Diabetes Mellitus is a disease in which an increase in blood sugar levels in the body (hyperglycemia), one of the complications of diabetic foot that can result in amputation and death with an incidence rate of 23.5% and 32.5%. Foot exercises is an effort to prevent the occurrence of foot complications in patients with diabetes mellitus. People with diabetes mellitus need to know about foot so well that the incidence of diabetic foot can be avoided. The purpose of this research is to level of knowledge about foot exercises with precautions of foot complications in patients with diabetes mellitus at Public Health Care Lubuk Begalung Padang 2018. This research type is analytical with cross sectional approach. Population of 414 and samples of 80 patients with diabetes mellitus with accidental sampling sampling technique. This research was conducted on 21 July - 4 August 2018 at Public Health Care Lubuk Begalung Padang Datas were collected through questionnaires, univariate data analysis is shown in the frequency distribution table and bivariate using chi-square. The results of this study found that 77.5% have low knowledge and 22.5% high knowledge, as much as 53.8% take good precautions and 46.2% take unfavorable precautions. From the results of statistical tests obtained p = 0.327. It can be concluded that there is no correlation between the level of knowledge about exercises foot with the prevention of foot complications in patients with diabetes mellitus at the Public Healt Care Puskesmas Lubuk Begalung Padang 2018. Therefore, it is expected to puskesmas staff to improve the counseling program and giving counseling about exercises foot, and the results of this study can be the basis for the next researcher. KERWORDS : Knowledge; Precautions; Diabetic Foot